2013
DOI: 10.1029/2012gb004453
|View full text |Cite
|
Sign up to set email alerts
|

Terrestrial dominance of organic matter in north temperate lakes

Abstract: [1] Aquatic ecosystems are hotspots of decomposition and sources of carbon dioxide to the atmosphere that are globally significant. Carbon exported from land (allochthonous) also supplements the carbon fixed by photosynthesis in aquatic ecosystems (autochthonous), contributing to the organic matter (OM) that supports aquatic consumers. Although the presence of terrestrial compounds in aquatic OM is well known, the contribution of terrestrial versus aquatic sources to the composition of OM has been quantified f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
112
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(126 citation statements)
references
References 68 publications
14
112
0
Order By: Relevance
“…The oligo-mesotrophic lakes are surrounded by forest (C 3 vegetation) and δ 13 C DOC was −28.0 ± 0.5 ‰, corresponding to a C 3 vegetation signal, suggesting that the DOC pool is dominantly terrestrially derived, consistent with a combined carbon and hydrogen isotope study of Wisconsin and Michigan lakes by Wilkinson et al (2013). The other proxy for allochthonous carbon, δ 13 C det , was slightly more negative (−29.6 ± 2.1 ‰), but the two proxies for allochthonous carbon were well correlated ( Table 2).…”
Section: Allochthonous δ 13 Csupporting
confidence: 75%
See 2 more Smart Citations
“…The oligo-mesotrophic lakes are surrounded by forest (C 3 vegetation) and δ 13 C DOC was −28.0 ± 0.5 ‰, corresponding to a C 3 vegetation signal, suggesting that the DOC pool is dominantly terrestrially derived, consistent with a combined carbon and hydrogen isotope study of Wisconsin and Michigan lakes by Wilkinson et al (2013). The other proxy for allochthonous carbon, δ 13 C det , was slightly more negative (−29.6 ± 2.1 ‰), but the two proxies for allochthonous carbon were well correlated ( Table 2).…”
Section: Allochthonous δ 13 Csupporting
confidence: 75%
“…The 1.6 ‰ lighter isotopic composition might reflect a relatively larger contribution of autochthonous detritus to the total detrital particulate organic matter pool than to the dissolved pool. Consistently with this, Wilkinson et al (2013) reported that a lower contribution of terrestrial organic matter to the particulate pool than to the dissolved organic matter pools in North American lakes.…”
Section: Allochthonous δ 13 Csupporting
confidence: 75%
See 1 more Smart Citation
“…Much of the dissolved organic matter (DOM) found in lakes typically represents between 90 and 100 % of the total carbon pool (Wilkinson et al, 2013) and is derived from terrestrial inputs, transported through streams, rivers and wetlands. This allochthonous component of the DOM originates from soils, sediments and plants and is primarily composed of humic substances.…”
Section: Importance Of Cdom In Lakesmentioning
confidence: 99%
“…In lakes, DOM is largely derived from terrestrial sources 3 and is central to food web dynamics [4][5][6] and global carbon cycling 7,8 . While oceans are the final receptacles of terrestrial DOM, transformations during transport through freshwater systems are important regulators of the ultimate quantity and quality of DOM delivered to marine systems [7][8][9][10] .…”
mentioning
confidence: 99%